Wealth inequality in South Africa: The role of government policy - Marlin Jason Fortuin; Gerhard Philip Maree Grebe; Patricia Lindelwa Rudo Makoni (Journal of Risk and Financial Management, 2022)
In South Africa, high levels of wealth inequality have persisted since 1994, to the extent that 1% of the population owns 50% of the wealth. This study examines how macroeconomic policies influenced wealth inequality in South Africa over the period 2010 to 2019 using a behavioural life-cycle model. Despite a decrease in wealth inequality over this period, the extent of this decrease is almost negligible. Results show government's current policy model to redirect wealth from a very small tax base that is under increasing financial strain is unable to meet wealth redistributive targets. The South African government should change the wealth redistribution policy from redistribution through predominantly lump sums to creating an environment in which private enterprises are able to absorb the labour capital that South Africa possesses. An open labour market would support private and foreign direct investment into the economy, thereby strengthening economic growth and upliftment through increased income and the consequent ability to accumulate wealth.
Keywords: 650; behavioural life cycle model; macroeconomic policy; quality of life; South Africa; wealth accumulation; wealth inequality; wealth redistribution